Regeneration of a Coastal Pine (Pinus thunbergii Parl.) Forest 11 Years after Thinning, Niigata, Japan - Zhu, Jiaojun (Public Library of Science, 2012)
To examine the effects of thinning intensity on wind vulnerability and regeneration in a coastal pine (Pinus thunbergii) forest, thinning with intensities of 20%, 30% and 50% was conducted in December 1997; there was an unthinned treatment as the control (total 8 stands). We re-measured the permanent sites to assess the regeneration characteristics 11 years after thinning. In the 50% thinned stand, seedlings aged from 2 to 10 years exhibited the highest pine seedling density and growth. The age composition ranged from 1–3 years with densities of 9.9 and 5.1 seedlings m(−2) in 30% and 20% thinned stands; only 1-year-old seedlings with a density of 6.1 seedlings m(−2) in the unthinned stand. Similar trends were found for the regeneration of broadleaved species such as Robinia pseudoacacia and Prunus serrulata. We speculate that the canopy openness and moss coverage contributed to the regeneration success in the 50% thinned stand, while the higher litter depth and lack of soil moisture induced the regeneration failure in the unthinned stand. The stands thinned at 20% or 30% were less favourable for pine regeneration than the stands thinned at 50%. Therefore, thinning with less than 30% canopy openness (20% and 30% thinned stands) should be avoided, and thinning at higher than 30% canopy openness (50% thinned stand, approximately 1500 stems ha(−1) at ages 40–50 years) is suggested for increasing regeneration in the coastal pine forest. The implications of thinning-based silviculture in the coastal pine forest management are also discussed. The ongoing development of the broadleaved seedlings calls for further observations.